Landscape of the Peripheral Immune Response Induced by Intraoperative Radiotherapy Combined with Surgery in Early Breast Cancer Patients - Danian Dai; Xuerui Li; Hongkai Zhuang; Yun Ling; Lezi Chen; Cheng Long; Jinhui Zhang; Yunjie Wang; Yuehua Li; Hailin Tang; Bo Chen (Advanced Science)
Abstract A comprehensive analysis of the immune response triggered by intraoperative radiation therapy (IORT) remains incomplete. In this study, single‐cell RNA sequencing and single‐cell T cell receptor sequencing are conducted on peripheral blood mononuclear cells (PBMCs) from patient with early‐stage breast cancer before and after IORT. Following IORT combined with surgery (defined as IORT+Surgery), PBMC counts remained stable, with increased proportions of T cells, mononuclear phagocytes, and plasma cells, and a reduction in neutrophil proportions. The cytotoxic score of CD8Teff_GZMK cells increased significantly post‐IORT. Communication between CD8Teff_GZMK cells and other immune cells via MIF_CD74 and MIF_TNFRSF14 is decreased after IORT. cDCs showed an upregulation of the MCH II signaling pathway, while memory B cells exhibited enhanced activation of the B cell pathway. T cell clones expanded significantly after treatment. IORT+Surgery demonstrated the ability to partially suppress the anti‐tumor effects of neutrophils. Flow cytometry analysis and co‐culture experiments are utilized to delve deeper into the functional alterations in T cells. IORT+Surgery significantly enhanced T cell cytotoxic activity. Blockade of PD‐1 of post‐IORT PBMCs shows higher T‐cell activity than that of pre‐IORT PBMCs. This research highlights IORT's impact on immune cells, offering insights for targeting immune responses in breast cancer.